A new Jehol enantiornithine bird with three-dimensional preservation and ovarian follicles. Issue 2 (3rd March 2016) - Wang, Yan; Wang, Min; O'Connor, Jingmai K.; Wang, Xiaoli; Zheng, Xiaoting; Zhang, Xiaomei
ABSTRACT: We report a new enantiornithine bird, Linyiornis amoena gen. et sp. nov., from the Lower Cretaceous Jiufotang Formation in northeastern China. Traces of ovarian follicles indicate that the specimen represents a female individual. The nearly three-dimensional preservation of the new specimen reveals morphological details rarely visible in other Early Cretaceous enantiornithines, allowing more detailed comparison with Late Cretaceous enantiornithines. Differences in the preserved morphology of the right and left coracoids suggest that the appearance of some features is strongly affected by preservation, indicating that the distribution of these features in compressed specimens may need to be reevaluated. Like Late Cretaceous enantiornithine specimens, the holotype of Linyiornis amoena preserves a hypertrophied pit for muscle attachment on the bicipital crest but clearly did not preserve a fossa for the capital ligament, present in Late Cretaceous taxa; we discuss the functional morphology and implications of these features in Linyiornis amoena . http://zoobank.org/urn:lsid:zoobank.org:pub:EFFD4348-7376-4201-A948-CEC686E2E0DC SUPPLEMENTAL DATA—Supplemental materials are available for this article for free at www.tandfonline.com/UJVP Citation for this article: Wang, Y., M. Wang, J. K. O'Connor, X. Wang, X. Zheng, and X. Zhang. 2016. A new Jehol enantiornithine bird with three-dimensional preservation and ovarian follicles. Journal of Vertebrate Paleontology. DOI: 10.1080/02724634.2015.1054496.